Sensory sustainable homes, a study of the healthy happy home (3H) conceptual design model: an explanatory qualitative study - Ekhaese, Eghosa; Hussain, Waqar; Ndimako, Onyedikachukwu O.; Hussain, Kifayat; Owoseni, Abraham (Frontiers in Sustainable Cities, 2025)
Sustainable homes support ecological, human, and economic health and vitality. Sensory sustainable homes (SSH) contextually mean creating a dwelling that integrates the concept ideas of the healthy elements, happiness determinants, and home requirements (3H) concept. The study resolved the investigator's question. What is the 3H conceptual design model? The study aims to investigate SSH design that integrates the 3H requirements into the conceptual model to enhance the occupants' quality of life (QoL). The article assessed expert opinions from relevant health and environmental professionals to identify the health elements in an SSH, identify the happiness determinants in SSH, and develop a conceptual framework that encapsulates the 3H design concept. The research employed a qualitative, exploratory-descriptive and contextual technique that leveraged phenomenological and ground theory approaches to create a new theory. A case study was the research design. The data was from 61 experts from the built environment and health professionals. The investigators identified 16 professions for the study. The researchers were the main research instrument in this study. Data collection instruments are an observation schedule, Focus Group Discussion (FGD), and an In-depth semi-structured Interview (IDI) guide to gather expert information to validate the 3H conceptual framework and SSH design checklist. The paradigm is post-positivism and interpretivism. Applying Maslow's hierarchy of needs and Sigmund Freud's pleasure principle, findings showed that architectural elements integrate occupants' health needs and pleasures into the home. It boosts happiness—a sense of aesthetics, security, belongingness, community, comfort, and peace. The 3H conceptual or SSH design results reveal that the architectural elements of a healthy home enhance happiness. Therefore, incorporating human needs and principles into a home can make the 3H design concept practical and hands-on.